Conjunctival metastasis of a renal cell carcinoma in a 59-year-old man – clinicopathological case report - Dernoga, Ewa; Rospond-Kubiak, Iwona; Kocięcki, Jarosław; Marszałek, Andrzej (Medical Studies/Studia Medyczne, 2016)
The aim of the study was to present a rare case of conjunctival metastasis of a renal cell carcinoma. A 59-year-old man presented in 2012 with rapidly growing, painless, and occasionally bleeding right eye conjunctival tumour. The patient had a history of advanced renal cell carcinoma diagnosed 3 weeks previously. The conjunctival tumour was resected, and histopathological report confirmed the working diagnosis of a metastatic tumour. The patient received palliative radiation to the central nervous system but died from disseminated disease 8 weeks later. Conjunctival metastasis of a renal cell carcinoma is exceedingly rare. It appears in a stage of disseminated disease.